Section 8 [videorecording (DVD)] - Law, Chad, 1979-; Ridgway, Josh; Kwanten, Ryan, 1976-; Lundgren, Dolph, 1959-; Mulroney, Dermot; Adkins, Scott, 1976-; Rourke, Mickey (RLJE Films, 2022)
After avenging the murder of his family, a former soldier is sprung from prison and recruited by a shadowy government agency.